Building supply-side resilience – a behavioural view. Issue 1 (14th August 2019) - Vanpoucke, Evelyne; Ellis, Scott C.
Abstract : Purpose: To build resilient supply chains, buyers should implement risk mitigation tactics. The purpose of this paper is to provide insights into the risky decision-making process that underlies buyers' decisions to adopt supply risk mitigation tactics for creating supply-side resilience. Design/methodology/approach: The authors employ experimental scenarios to simulate supply disruptions of low and high likelihood. The authors then assess buyers' decisions to adopt supply risk mitigation tactics in response to these scenarios. Findings: The authors find that buyers' perceptions of supply disruption likelihood are positively related to their adoption of buffer- and process-oriented risk mitigation tactics and preference for process-oriented risk mitigation tactics. Conversely, risk propensity negatively affects buyers' adoption of buffer- and process-oriented mitigation tactics. Originality/value: Beyond risk perceptions, the authors consider how risk propensity also affects the risky decision-making process. Moreover, whereas previous studies often focus on a single mitigation tactic, the authors study buyers' adoption of multiple buffer- and process-oriented risk mitigation tactics to create supply-side resilience.